2013
DOI: 10.1371/journal.pone.0055493
|View full text |Cite
|
Sign up to set email alerts
|

An Inverse Switch in DNA Base Excision and Strand Break Repair Contributes to Melphalan Resistance in Multiple Myeloma Cells

Abstract: Alterations in checkpoint and DNA repair pathways may provide adaptive mechanisms contributing to acquired drug resistance. Here, we investigated the levels of proteins mediating DNA damage signaling and -repair in RPMI8226 multiple myeloma cells and its Melphalan-resistant derivative 8226-LR5. We observed markedly reduced steady-state levels of DNA glycosylases UNG2, NEIL1 and MPG in the resistant cells and cross-resistance to agents inducing their respective DNA base lesions. Conversely, repair of alkali-lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 72 publications
4
20
0
Order By: Relevance
“…We found that gH2AX foci reached maximal levels within 8 hours and decreased thereafter. In accordance with previous data showing that melphalan-induced gH2AX foci persist for a shorter time in melphalanresistant LR5 cells, 28 we found that RPMI 8226 cells showed BLOOD significantly lower gH2AX foci removal capacity and higher gH2AX foci burden than LR5 cells (Figure 2F-I; supplemental Table 1). All DSB/R inhibitors increased the accumulation of gH2AX in both cell lines (Figure 2G-I).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…We found that gH2AX foci reached maximal levels within 8 hours and decreased thereafter. In accordance with previous data showing that melphalan-induced gH2AX foci persist for a shorter time in melphalanresistant LR5 cells, 28 we found that RPMI 8226 cells showed BLOOD significantly lower gH2AX foci removal capacity and higher gH2AX foci burden than LR5 cells (Figure 2F-I; supplemental Table 1). All DSB/R inhibitors increased the accumulation of gH2AX in both cell lines (Figure 2G-I).…”
Section: Resultssupporting
confidence: 93%
“…All DSB/R inhibitors increased the accumulation of gH2AX in both cell lines (Figure 2G-I). It is worth mentioning that, in line with the high levels of ligase IV observed in these cell lines, 28 we found that SCR7 showed the strongest effect. In harmony with gH2AX foci formation, Rad51 foci reached maximal levels within 8 hours and decreased thereafter, whereas LR5 cells showed lower levels of Rad51 foci compared with RPMI 8226 cells (Figure 2J-M; supplemental Table 1).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations